2018
DOI: 10.1051/0004-6361/201833300
|View full text |Cite
|
Sign up to set email alerts
|

First observations of magnetic holes deep within the coma of a comet

Abstract: The Rosetta spacecraft of the European Space Agency made ground-breaking observations of comet 67P/Churyumov-Gerasimenko and of its cometary environment. We search for magnetic holes in that environment, i.e., significant depressions in the magnetic field strength, measured by the Rosetta fluxgate Magnetometer (MAG) in April and May 2015. In that time frame of two months, we identified 23 magnetic holes. The cometary activity was intermediate and increasing because Rosetta was on the inbound leg toward the Sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 66 publications
3
35
0
Order By: Relevance
“…However, these structures will interact with the bow shock and propagate downstream into the magnetosheath. At comets, MHs can travel to very low altitudes, while their structure becomes compressed (Plaschke et al, 2018). At planets with an intrinsic magnetosphere, such as Mercury and Earth, solar wind MHs survive the bow shock and travel through the magnetosheath in the form of diamagnetic plasmoids (Karlsson et al, 2015(Karlsson et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…However, these structures will interact with the bow shock and propagate downstream into the magnetosheath. At comets, MHs can travel to very low altitudes, while their structure becomes compressed (Plaschke et al, 2018). At planets with an intrinsic magnetosphere, such as Mercury and Earth, solar wind MHs survive the bow shock and travel through the magnetosheath in the form of diamagnetic plasmoids (Karlsson et al, 2015(Karlsson et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic field data are investigated for the presence of magnetic holes. In this paper the same method is used as in Plaschke et al (2018). A short recap is as follows.…”
Section: Magnetic Hole Finding Methodsmentioning
confidence: 99%
“…This resulted in the green line with D(B) = a exp{−bB} + c with a = −0.53 ± 0.07, b = 0.17 ± 0.06 nT −1 , and c = 0.93 ± 0.06. Qu et al (2007) discussed the gyro-kinetic model of the MM instability and found growth rates of the order of γ MM ∝ 10 −2 i , where i is the ion cyclotron frequency. Based on only linear growth of the structures this would indicate that for stronger B stronger MMs can be expected; however, it should be expected that non-linear behaviour will set in at some point.…”
Section: Magnetic Field Strengthmentioning
confidence: 99%
“…Earth, solar wind MHs survive the bow shock and travel through the magnetosheath in the form of diamagnetic plasmoids (Karlsson et al, 2015(Karlsson et al, , 2016. At comets MHs can travel to very low altitudes while their structure becomes compressed (Plaschke et al, 2018). We acknowledge the MAVEN contract for support.…”
mentioning
confidence: 99%